Mekanisme Pemeliharaan Aset dalam Pengelolaan Barag Milik Daerah di Dinas Kesehatan Kabupaten Sumenep - Mohammad Faizal Amir; Mohamad Djasuli (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2016)
The purpose of this study is to investigate the process of maintenance and asset management area, knowing the efforts undertaken to optimize the utilization in the asset management area in Sumenep regency. This research uses descriptive qualitative research method. The primary data obtained through interwiew committed against Ka.Bid the procurement of goods, used in the form of legislation, evidence, history and other data that acts as a support in this study.The data collection  procedures by interview and documentation. Based on the data obtained from the Health Department of Sumenep, in the maintenance and management as well as efforts to optimize the utilization of the property of local government Sumenep Regency has been guided by the Regulation number 17 in 2007. There was also the need for better coordination to realize the smooth conduct maintenance management property in the District of Sumenep.